Subtype-specific pattern of white blood cell differential in endogenous hypercortisolism. Issue 3 (29th July 2022) - Detomas, Mario; Altieri, Barbara; Chifu, Irina; Remde, Hanna; Zhou, Xiang; Landwehr, Laura-Sophie; Sbiera, Silviu; Kroiss, Matthias; Fassnacht, Martin; Deutschbein, Timo
Abstract: Objective: Endogenous hypercortisolism predisposes to impaired immune function and infections. To date, however, it is unknown whether there is a subtype-specific pattern in white blood cell (WBC) and WBC differential (WBCD) count. Methods: A retrospective monocentric cohort study was carried out in patients with overt endogenous Cushing's syndrome (CS) or adrenal incidentalomas and autonomous cortisol secretion (ACS), with WBC/WBCD analysis at initial diagnosis and after biochemical remission. Cut-offs were obtained by receiver-operating characteristics analysis. Results: In total, 253 patients were analyzed (Cushing's disease (CD); n   = 88; ectopic CS (ECS), n   = 31; cortisol-producing adrenal adenomas (CPA), n   = 40; ACS, n   = 45; adrenocortical carcinomas (ACC), n   = 49). Total leukocytes and neutrophils correlated positively with serum cortisol after 1-mg dexamethasone (r = 0.314 and r = 0.428), while a negative correlation was observed for lymphocytes and eosinophils (r = −0.374 and r= −0.380) (each P  < 0.0001). Similar observations were made for 24 h-urinary free cortisol. CD and ECS differed in numbers of neutrophils and lymphocytes ( P  < 0.0001) and were well differentiated at a cut-off of 6.1 for the neutrophil/lymphocyte ratio (sensitivity 90.0%, specificity 89.4%, and areas under the curve (AUC) 0.918). For adrenocorticotropic hormone (ACTH)-independent CS, the best diagnostic outcome was obtained for the discrimination of CPA and ACC at a cut-off of 187.9 for the platelet/lymphocyte ratio (sensitivity 59.6%, specificity 80.6%, and AUC 0.713). For ECS, CPA, and CD, neutrophils decreased (delta −47.0, −29.7, and −26.2%) and lymphocytes increased (+123.2, +78.1, and +17.7%) already 3 months after remission. Conclusion: Most immune cells correlate with the degree of hypercortisolism and differ among CS subtypes. WBCD changes are already identified 3 months after remission from endogenous hypercortisolism.